Keputusan Investasi Saham Dengan Pendekatan Price Earning Ratio Pada Perusahaan Rokok yang Terdaftar di Bursa Efek Indonesia - Seno Hadi Saputro; Kartika Yuliantari (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2020)
Investing in the capital market is one way to improve investor welfare in the future. Investors invest in the capital market to benefit from the funds invested sourced from businesses that have funds. This study aims to analyze stock investment decisions with the Price Earning Ratio approach to cigarette companies listed on the Indonesian stock exchange. This type of research is applied research (Applied Research) with descriptive quantitative analysis. In this study, sampling was conducted based on purposive sampling method with sample criteria, namely companies listed on the Indonesia Stock Exchange from December 2015 - September 2019 and showed positive profits from December 2015 - September 2019. The results of this study are warehouses Garam Tbk, HM Sampoerna Tbk and Wismilak Inti Makmur Tbk are in an Undervalued condition and if the company is in these conditions it is recommended to buy these shares or if they already have can add to their shares. Keywords: stock investment, Price Earning Ratio, cigarette company